2019
DOI: 10.12659/ajcr.917159
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Diffuse Large B Cell Lymphoma Presenting as a Cardiac Mass

Abstract: Rare disease Background: Primary mediastinal diffuse large B cell lymphoma (DLBCL) presenting as a large intracardiac tumor is extremely rare and has not been significantly reported in the literature. Cardiac lymphoma consists of 2 subtypes: mediastinal DLBCL invading the heart and primary cardiac lymphoma. Both subtypes have a poor prognosis and are treated similarly. Mediastinal DLBCL is a life-threatening condition that, if diagnosed early, has a better survival rate. This is a rare case of a mediastinal DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Cardiac involvement by NHL is rare, and to be presented as intracardiac mass is extremely rare. It could be a primary cardiac lymphoma or mediastinal mass with direct extension and in ltration into the right atrium giving a picture of intracardiac mass (3)(4)(5)(6). The prognosis of both subtypes are poor due to rapid progression and invasion of the disease with detection usually in the late stage of the disease (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac involvement by NHL is rare, and to be presented as intracardiac mass is extremely rare. It could be a primary cardiac lymphoma or mediastinal mass with direct extension and in ltration into the right atrium giving a picture of intracardiac mass (3)(4)(5)(6). The prognosis of both subtypes are poor due to rapid progression and invasion of the disease with detection usually in the late stage of the disease (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-cardiac mass is a very rare presentation of DLBL (3)(4)(5)(6). This is a case report of a 26-year-old immunocompetent female patient presenting with gross intracardiac mass and Superior Vena Cava syndrome.…”
Section: Introductionmentioning
confidence: 94%
“…The right atrium [24] and ventricle are usually involved [25], and biatrial cases were reported [26]. Rare sporadic PCLs were reported in the left ventricle [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, echocardiography still showed extensive involvement in the aorta, peripulmonary arteries, left ventricle, and left atrium ( Figure 2D ), suggesting a poor prognosis. 5 One month after this follow-up, the patient succumbed to death owing to a sudden episode of ventricular tachycardia, ventricular fibrillation, and decreased blood pressure despite resuscitation efforts ( Figure 3 ).…”
Section: Case Presentationmentioning
confidence: 99%